Expectations of adolescents to receive reproductive health information and services from health service system: A qualitative study in Bangladesh - Yunus, Samiha; Sharmin, Sabrina; Huq, Nafisa Lira; Haseen, Fariha; Imam, Md Ali; Nahar, Quamrun (South East Asia Journal of Public Health, 2018)
Adolescents, aged 10-19 years, constitute one fifth of Bangladesh's total population of 158 million. Similar to adolescents elsewhere, Bangladeshi adolescents also have special sexual and reproductive health (SRH) information and service needs; however, these needs are not adequately addressed by the existing health service system. The present study was conducted to identify adolescents’ expectations of and preferences for receiving SRH information and services. This qualitative study was conducted in six purposively selected areas of Bangladesh using 20 Key Informant Interviews (KII) during September-November 2012. Key informants aged between 15 to 19 years were leaders of youth organizations or class monitors in school. Informants were unmarried and married, males and females, and from rural and urban areas. This study identified that there is a strong need for SRH services for adolescents. Irrespective of their residence and gender, adolescents preferred health service providers to be qualified medical doctors, who are experienced, well-trained and polite. Availability of doctors, maintaining privacy and treatment through counseling were mentioned as their priorities. Both urban and rural adolescents recommended establishing adolescent friendly environment in every government and NGO health service facility. They also asked for gender specific service provider for female and male adolescents. Urban adolescents expressed the need for school health program with provision of school health clinics. On the other hand, rural adolescents recommended for community health workers to raise awareness on adolescent sexual and reproductive health (ASRH) issues with parents and families. The adolescents also expected to receive SRH information through mass media, school curriculum, and booklets on adolescent SRH, and peer educator. Addressing the expectations of adolescents will open a new skylight to policy makers to design highly accessible health services for adolescents in Bangladesh South East Asia Journal of Public Health Vol.7(2) 2017: 19-26